Effects of silane coupling agent modifications of hollow glass microspheres on syntactic foams with epoxy matrix. Issue 9 (November 2021) - Li, Rui; Fan, Guisen; Wang, Peng; Ouyang, Xiao; Ma, Ning; Wei, Hao
A syntactic foam was prepared from an epoxy resin matrix and modified hollow glass microsphere fillers. Modification by silane coupling agents with different molecular structures was analyzed, and the optimal content of the silane coupling agent was determined. The results demonstrated that all silane coupling agents enhanced the adhesion between the hollow glass microspheres and epoxy resin matrix, resulting in enhanced water absorption, compressive performance, tensile performance, and bending performance compared to those prepared using unmodified hollow glass microspheres. Among silane coupling agents with different end groups, the one with a sulfhydryl end group exhibited optimal modification for hollow glass microspheres. Among the silane coupling agents with different backbone structures, the one with silanol groups exhibited the optimal modification of hollow glass microspheres. Additionally, the performance of the syntactic foams was optimal when 6% of the silanol-containing coupling agent was used. The results demonstrated that syntactic foams prepared with hollow glass microspheres modified by silane coupling agents exhibited improvements in water absorption, compressive performance, tensile performance, and bending performance, compared with those prepared using unmodified hollow glass microspheres. Among silane coupling agents with different end structures, the one with a sulfhydryl group as end group showed the best modification effect on hollow glass microspheres. The water absorption was 0.35%, the compressive strength was 62.15 MPa, the tensile strength was 40.15 MPa, and the bending strength was 53.17 MPa. Among silane coupling agents with different backbone structures, the one with silanol groupsbonds showed the best results. Its compressive strength was up to 64.15 MPa, the tensile strength was 35.47 MPa, and the bending strength was 53.99 MPa.